2015
DOI: 10.1021/acs.langmuir.5b00774
|View full text |Cite
|
Sign up to set email alerts
|

Electrohydrodynamic Deformation and Rotation of a Particle-Coated Drop

Abstract: A dielectric drop suspended in conducting liquid and subjected to an uniform electric field deforms into an ellipsoid whose major axis is either perpendicular or tilted (due to Quincke rotation effect) relative to the applied field. We experimentally study the effect of surface-adsorbed colloidal particles on these classic electrohydrodynamic phenomena. We observe that at high surface coverage (> 90%), the electrohydrodynamic flow is suppressed, oblate drop deformation is enhanced, and the threshold for tilt i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 64 publications
(164 reference statements)
2
36
0
Order By: Relevance
“…A similar behavior is observed for pure PS particles and PS particles sulfonated for 2 min (not shown here). The direction of the EHD flows and the droplet deformation are determined by the ratios between the conductivities and dielectric constant of the fluids [23,63,64]. In our case, the surrounding castor oil conducts approximately 10 times better than the silicone oil, thus resulting in an oblate deformation (droplet axis perpendicular to the electric field direction is larger than the axis parallel to the electric field direction), and the EHD flows are directed from droplet electric poles to the electric equator [16].…”
Section: Resultsmentioning
confidence: 99%
“…A similar behavior is observed for pure PS particles and PS particles sulfonated for 2 min (not shown here). The direction of the EHD flows and the droplet deformation are determined by the ratios between the conductivities and dielectric constant of the fluids [23,63,64]. In our case, the surrounding castor oil conducts approximately 10 times better than the silicone oil, thus resulting in an oblate deformation (droplet axis perpendicular to the electric field direction is larger than the axis parallel to the electric field direction), and the EHD flows are directed from droplet electric poles to the electric equator [16].…”
Section: Resultsmentioning
confidence: 99%
“…It has also been demonstrated that emulsion drops can undergo Quincke rotation [10,11,12]. Here we investigate the interaction of two Quincke rotating particle covered drops (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanics of particle-laden droplets has recently been studied using a variety of approaches [10][11][12][13][14][15][16][17]. The compression of particle-laden droplets, whose radii are in the vicinity of 10 µm, using Scanning Force Microscopy [10] or Atomic Force Microscopy [11] revealed substantial deviations from the elastic shell models, with apparent contributions from surface tension.…”
Section: Pacs Numbers: I Introductionmentioning
confidence: 99%